Sinonasal teratocarcinosarcoma: a rare case report from a tertiary care centre of North East India - Bharadwaj, Barasha S.; Suhana, Asreen; Deka, Muktanjalee; Sharma, Jagannath D.; Beso, Adahra P.; Kalita, Upasana; Goswami , Bibhash C. (International Journal of Research in Medical Sciences, 2023)
Sinonasal teratocarcinosarcoma is an extremely rare malignant tumour arising in the sinonasal tract, that may extend intracranially to complicate the treatment and further worsen its dismal prognosis. Diagnosis is challenging because of its rarity and morphologic heterogeneity. Here, we reported a case of a 55 years old male who presented with complaints of left sided nasal blockage and facial swelling. CECT showed a large sinonasal mass with epicentre in the left nasal cavity extending to post nasal space and nasopharynx, eroding the left medial orbital wall and cranially the cribriform plate. Histopathologically, malignant epithelial component comprising of squamous cell carcinoma, mesenchymal component comprising of fibrosarcoma with focal chondroid differentiation, primitive blastemal component with extensive necrosis was noted. Immunohistochemistry demonstrated positivity for synaptophysin, chromogranin, Pan-CK, EMA, CD99, focal p63 in areas of squamous metaplasia; stromal cells showed Desmin, S100, SOX 10 expression: Ki-67 was 30-40%. Immunohistochemistry confirmed the diagnosis of sinonasal teratocarcinosarcoma. Knowledge about this tumour is important because of its heterogenous morphology which often leads to a misdiagnosis, necessitating repeated biopsies and thorough examination of the surgical specimen.